SARCOPTES SCABIEI INFECTION IN POMERANIA MIXED DOG - Ni Komang Wijayani; Sri Kayati Widyastuti; I Nyoman Suartha (Buletin Veteriner Udayana, 2025)
Scabies is a skin disease caused by the mite Sarcoptes scabiei which is zoonotic. This case report aims to add information about scabiosis cases and treatments that can be done on dogs. Examination of a Pomeranian crossbreed dog named Putri, a 6-year-old female weighing 3 kg, has been experiencing itching since 3 months ago. Physical examination showed alopecia almost all over the body, severe hyperkeratosis on the left ear and crusting on the cranial extremities dexter and sinister, head area and neck area. Superficial skin scraping and deep skin scraping examination found Sarcoptes scabiei mites while hematology examination showed hypochromic microcytic anemia. Based on a series of examinations that have been carried out, the disease was diagnosed as suffering from Scabies infection. The therapy given was ivermectin 1% given as much as 0.1 ml SC, Chlorpheniramine maleate given as much as ¼ tablet PO BID for 5 days, fish oil and vitamin PO SID for 16 days and the dog was bathed 2 times a week with Sebasol shampoo. Evaluation of therapy on the 16th day showed good development marked by the dog experiencing a decrease in the frequency of pruritus, lesions such as crusts and hyperkeratosis on the body had disappeared. Alopecia decreased marked by hair growth in areas experiencing alopecia.